Improving students' attitudes about corporate social responsibility via 'Apps': a perspective integrating elaboration likelihood model and social media capabilities. Issue 8 (3rd August 2021) - Zhang, Xi; Zhou, Shuling; Yu, Yao; Cheng, Yihang; de Pablos, Patricia Ordóñez; Lytras, Miltiadis D.
ABSTRACT: In recent years, online education has boomed. However, online business ethics education faces a challenge in which the lack of communication among teachers and students leads to a decline in teaching effectiveness. Social media applications can be imbedded in traditional ethics education to solve this problem. In this paper, based on the elaboration likelihood model and social media capabilities theory, we develop an integrated model to explain how the change in students' attitudes about corporate social responsibility (CSR) happens in a social media-supported environment and how social media capabilities affect the processes. We conducted a teaching experiment and collected 233 valid samples of students to verify the hypothesis. Our study confirmed there are two mechanisms to affect students' attitudes about CSR, source credibility, and argument quality. Concurrency has a moderating effect on attitudes change. Possible reasons, limitations, implications, and advice for future studies are also presented.